Searching, coordinating and analyzing of tea literature published in China - ZHU Yong-xing; ZHOU Ju-gen (浙江大学学报. 农业与生命科学版)
More than 20 thousands papers on tea science were searched and collected from all accessible resources, using the most advanced technologies of network, information and database. A database system with index tools on tea literature were developed, including patent literature, newspaper articles and journal papers relevant to tea science. With this database system on tea literature published in journals were statistically analyzed. The results showed that 21206 papers were published in the last decade or so, being distributed in 2073 publishing media and involving 9132 authors (the first author) who belong to 6697 institutions. The developing trend on published papers, authors, institutions with which the authors were affiliated and the journals by which original papres on tea were published during the last decade or so were statistically analyzed and discussed.